The relationships between wear behavior and thermal conductivity of CuSn/M7C3-M23C6 composites at ambient and elevated temperatures - Yilmaz, O; Turhan, H (Elsevier Sci Ltd, 2001)
The effect of FeCr (M7C3-M23C6) particles on the wear resistance of a CuSn alloy was investigated under 125 N load, and 300-475 K temperature interval. Sliding tests were performed to investigate the wear behavior of FeCrp-reinforced CuSn metal-matrix composites (MMCs) against DIN 5401 in a block-on-ring apparatus. The CuSn/FeCrp MMCs, which were prepared by addition of 5, 10, 15 and 20 vol.% of FeCrp, were produced by powder metallurgy and the size of the particles was taken as 16 mum. The powders were uniaxially cold compacted by increasing pressure up to 250 Mpa. The dry sliding wear tests were carried out in an incremental manner, i.e. 300 in per increment and 3500 in total sliding length. The wear-test results were used for investigation of the relationship between weight loss, microstructure, surface hardness, friction coefficient, particle content and thermal conductivity. Finally, it was observed that FeCrp reinforcement is beneficial in increasing the wear resistance of CuSn MMCs. FeCr particles in MMCs also tend to reduce the extent of plastic deformation in the subsurface region of the matrix, thereby delaying the nucleation and propagation of subsurface microcracks (C) 2001 Published by Elsevier Science Ltd. All rights reserved.
Keywords: MMCs; thermal properties; delamination; DTA-SEM